Assoclation polymorphism apoe gene and blood lipid profile with diffe different types of stroke in Siberia - M. I. Voevoda; Yu. V. Skurikhina; S. V. Shishkin (Бюллетень сибирской медицины, 2011)
The present research aimed at studying association between Apo E polymorphism and certain types of stroke and also association factors of lipid profile’s results and different types of stroke it depends on sex and conditions of living in typical West Siberian megapolis (Novosibirsk).The causes of brain stroke were registered in representative population with population about 150 000 in according to standarts of WHO program MONICA and previous program «Register of stroke». From 2003 to 2007 among new registered and repeated causes of stroke was form at random 15% sample (261 patients). The average age of stroke attack is 61,3 ± 1,0 for men and 61,3 ± 1,0 for women.Independent influence of APOE gene's genotypes polymorphism on development at different stroke patients has not been revealed.